Design of a miniaturized HF antenna - Lim, Wee Lee (2014)
This final year project was to study miniaturization techniques to reduce the size of a High Frequency (HF) antenna while retaining its wide-band radiation characteristics. The HF antenna operating at a frequency of 2MHz to 30MHz is to be placed above a building. Some of the miniaturization techniques investigated in this project includes the different ways of bending the antenna wires. Theoretical simulation will be conducted using Ansoft’s High Frequency Structure Simulator (HFSS).